The effect of internal control systems and procrastination on public sector employees - Zahari, Afzal Izzaz; Said, Jamaliah; Arshad, Roshayani (OMJP Alpha Publishing, 2019)
Internal control is a control mechanism that keeps in check the structure for it to operate within the intended parameters and target objectives. The paper offers an overview effectiveness of internal control on whether it achieves the purpose of control the organisation in reducing the laziness in public sector employees. The overall design approach is through the analysis of internal control systems from the Committee of Sponsoring Organisation (COSO) framework. Data was collected through the distribution of questionnaires towards 106 government organisations based on the contents of five components of internal control, which consist of the control environment, risk assessment, control activities, information and monitoring activities. A total sample of 118 government employees returned the questionnaires. Through the analysis of the internal control system, the overview is then observed on whether it would improve overall organisational performance. The study indicated that only a single component of internal control systems (monitoring) is an effective mechanism towards reducing procrastination. The usefulness on whether having strong controls can improve overall organisation performance in the public sector provides a different perspective as government employees have different motivations from private sector employees. The paper contributes towards understanding human behavior in terms of its reaction towards control systems. It is also from a public sector viewpoint of which internal control effectiveness must be strong in order to increase effectiveness.